2010
DOI: 10.1007/s10354-010-0818-x
|View full text |Cite
|
Sign up to set email alerts
|

Levels of osteoprotegerin (OPG) and receptor activator for nuclear factor kappa B ligand (RANKL) in serum: Are they of any help?

Abstract: The coupling of bone formation and resorption is mediated through the OPG/RANK/RANKL system. OPG and RANKL are mainly produced by osteoblasts but also a variety of other tissues. The binding of RANKL to RANK, its natural receptor which is expressed by osteoclasts, accelerates bone resorption. OPG acts as decoy receptor and prevents the interaction of RANKL with RANK and therefore leads to a decrease in activity, survival and proliferation of osteoclasts. Since assays for measurements of serum OPG and RANKL hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 70 publications
(109 reference statements)
2
32
0
1
Order By: Relevance
“…It has been demonstrated that pro-inflammatory cytokines influence the bone tissue directly and/or indirectly, via the RANKL/RANK/OPG system [27][28][29][30][31][32][33][34][35][36][37][38][39]. Since it has been documented that IL-1β, IL-6, and TNF-α stimulate bone resorption both in vitro and in vivo [27][28][29][30], it seems reasonable to presume that any potential disturbances in the production of these cytokines in patients with AN might play a role in the development of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that pro-inflammatory cytokines influence the bone tissue directly and/or indirectly, via the RANKL/RANK/OPG system [27][28][29][30][31][32][33][34][35][36][37][38][39]. Since it has been documented that IL-1β, IL-6, and TNF-α stimulate bone resorption both in vitro and in vivo [27][28][29][30], it seems reasonable to presume that any potential disturbances in the production of these cytokines in patients with AN might play a role in the development of osteoporosis.…”
Section: Discussionmentioning
confidence: 99%
“…The above data suggest that cytokines may regulate osteoclastogenesis not only directly, but also indirectly via the RANKL/ /RANK/OPG system [27][28][29][30][31][32][33][34][35][36][37][38][39]. Through an increase in the expression of RANKL and/or a decrease in OPG expression, IL-1β, IL-6, or TNF-α may suppress the OPG/RANKL ratio resulting in enhanced bone resorption [27][28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Prace Oryginalnementioning
confidence: 99%
See 1 more Smart Citation
“…These disorders might be imposed predominantly by the changes occurring directly in tumor tissue, but we cannot ignore the fact that serum levels of RANK/RANKL/OPG components, as well as the level of any other serological marker, cannot be completely determined by the secretion of corresponding protein from tumor cells. It depends on various physiological factors, on probable production of proteins studied by other tissues, and on the presence of concomitant diseases, in particular, osteoporosis and inflammatory processes [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…Studies demonstrated that cementoblasts that were stimulated by mechanical signals affected cementoblast functions (Brezniak and Wasserstein, 2002). Osteoprotegerin (OPG) and receptor activator of nuclear factor-κB ligand (RANKL) were thought to be widely involved in the growth of bone cells (Rody et al, 2001;Wagner and Fahrleitner-Pammer, 2010). However, whether mechanical stimulation affected the expression of OPG, RANKL, and runt-related transcription factor-2 (RUNX2) remained unclear.…”
Section: Introductionmentioning
confidence: 99%